Social infrastructures: a shift to decentralized infrastructure as a means of rejuvenating blighted Lagosian contexts and places of similar genus - Windapo, Bayonle Olanrewaju (School of Architecture, Planning and Geomatics, 2016)
This research stems from reports of the interaction between the growing informal communities such as Makoko, the coastal plains of the degenerating Lagos contexts and their limited access to central infrastructure. The effects of climate change on the low-lying coastal plains further exacerbate the degeneration experienced in these contexts. Therefore this research examines how people live independently of central infrastructure in informal contexts such as Makoko and whether this autonomy can be embedded into interventions that are integrated within the socio-economic networks of these contexts in a bid to shift from defective central infrastructures to social infrastructures that transform the blighted Lagos contexts in a manner that builds resilience at a local level. By using Makoko as a site for exploration and communicating with the locals of the context, Lagos professionals and non-governmental organizations, it emerged that there is currently an unhealthy relationship between the state, its local governments and its informal communities such as Makoko, in that the city of Lagos is managed principally from the office of the governor. This central management results in infrastructures that are implemented without critical acknowledgement of the problems faced by individuals who live in the many informal contexts of Lagos thereby resulting in little or no observable transformation in its (Lagos) degenerating contexts. It was also observed that Makoko has a unique urbanity of soft infrastructures that lend themselves to different scales of functions in the context and diverge from the typical hard infrastructures employed by the Lagos state government. The observations and findings point to the fact that the relationship between the state and its people must be strengthened for delivered infrastructures to be of any consequence in realizing any positive social change and transform Lagos and settlements like Makoko from their states of human and environmental degeneration by acknowledging that these contexts have unique problems and urbanisms that must be fused into any interventions within their precincts in a sustainable, ecological and economical way. This move will go a long way in transforming and legitimizing Lagos's degenerating contexts as important facets of the city.